Alterations in retinal nerve fiber layer thickness in early stages of diabetic retinopathy and potential risk factors. (1st February 2018) - Shi, Rui; Guo, Zhonglan; Wang, Feng; Li, Rong; Zhao, Lei; Lin, Rong
ABSTRACT: Aims : To investigate the loss of retinal nerve fiber layer (RNFL) in type-2 diabetic patients with early-stage diabetic retinopathy (DR) and to identify potential risk factors accounting for these alterations. Methods : In this cross-sectional study, 158 type-2 diabetic patients were divided into three groups based on their DR status. RNFL thickness and other optic disc parameters were obtained by optical coherence tomography (OCT) and then compared among different groups. We investigated the potential association between RNFL loss and systemic risk factors for DR, including diabetes duration, body mass index (BMI), serum lipids, hemoglobin A1c (HbA1c) and albumin-creatinine ratio (ACR). One-way ANOVA was carried out to compare RNFL thickness among different groups, Pearson correlation and multivariate linear regression analysis were performed to determine potential risk factors related to RNFL thickness in these patients. Results : There were significant differences in the average ( F = 8.872, P = 0.003), superior ( F = 8.769, P = 0.004), and inferior ( F = 8.857, P = 0.003) RNFL thickness of both eyes among the groups, but no obvious difference in optic disc parameters was found. Diabetic duration, BMI, TG, High density lipoprotein cholesterol (HDL), HbA1c, and ACR were found negatively related to the RNFL thickness in both or single eye according to Pearson correlation analysis. After controlling for age, gender, and axis length (AL) in multivariate linear regression analysis, the diabetic duration was associated significantly with RNFL thickness of superior in both eye (right eye: p = 0.016, left eye: p = 0.024 ), BMI was related to the nasal quadrant of the right eye ( p = 0.034 ), and TG was related to the inferior of the right eye ( p = 0.037 ), HbA1c ( p = 0.026 ) was associated significantly with the average RNFL thickness of the right eye. In addition, ACR was found negatively related to average ( p = 0.042 ) and inferior quadrant ( p = 0.014 ) of the left eye, respectively. Conclusions : RNFL loss might be the earliest structural change of retina in diabetic patients, and associated with diabetic duration, BMI, TG, HbA1c, and ACR. The conclusions of this study need to be proved by other well-matched and large-scale prospective clinical trials in the future, because the correlations discovered in our study were weak.